Contamination of E.coli Bacteria in Spamdus Genjahan Water Distribution Network from Karst Groundwater Source - Eko Budiyanto; Nugroho Hari Purnomo; Muzayanah Muzayanah; Aida Kurniawati (Geosfera Indonesia, 2024)
Karst groundwater is raw water used by Spamdus Genjahan to fulfill domestic water needs. Considering the vulnerability of karst groundwater to pollution and its distribution process, the research aimed to describe the suitability of water in the network as well as the spatial distribution of E.coli and the relationship between distance and it’s concentration. The concentration of E.coli was tested from water samples taken from 20 outlets as representatives of the close, medium and farthest distances from the source. The feasibility of water is carried out by comparing the results of laboratory tests with the water quality threshold value for clean water and domestic purposes. Spatial distribution was analyzed through spatial analysis using Geographic Information Systems, while the relationship between distance and E.coli concentration was carried out using the scatterplot method in GIS. The results showed that the concentration of E.coli in most of the samples was above the allowable threshold for sanitation hygiene purposes. Meanwhile, the distance from the outlet to the source did not show a strong correlation with the level of E.coli concentration. However, there are weak indications that lead to an increase in concentration with the E.coli.